MR Imaging Features of Primary Mucosal Melanoma of the Eustachian Tube: Report of 2 Cases - Yang, B.T. (AJNR Am J Neuroradiol, 2009)
SUMMARY: We observed 2 cases of malignant melanoma arising from the eustachian tube with MR imaging. In this region, we explored further characteristics of primary mucosal melanoma. We discuss the value of using MR imaging to diagnose and treat patients with melanoma in the eustachian tube. In addition, we introduce the key points to differentiate melanoma from some common diseases in the region.